Shaping self through ceramic sculpture: representing anxiety in the rural black queer experience - Phaliso, Phila Vuyiseka (Rhodes University, Faculty of Humanities, Department of Fine Art)
I am a ceramic sculptor. I make use of clay that I have sourced from Joza, the Makhanda location, and Cofimvaba in a rural area called Magwala. I process this clay and then use it to create a visual and tangible representation of the anxiety I experience as a queer black woman living in South Africa. Unongayindoda is a word that has been used by isiXhosa speaking people in my village to call me ever since I was a child. This is a word that I have chosen to own, in much the same way that some people have chosen to own the word "queer." My experience of being unongayindoda has had an impact on my mental health, and the process of digging clay, processing it for use and then using it to create my work has become very therapeutic for me. My work's primary aim is to explore the use of clay as a representative embodiment of anxiety in my work as a rural black queer sculptor who identifies as unongayindoda. The thesis component of my work is a qualitative study informed by autoethnography, practice and art-based research.
Keywords: Ceramic sculpture -- 21st century; Ceramic sculpture -- Social aspects; Sexual minorities, Black -- Social conditions; Anxiety; Rural conditions in art